ANALISIS EFEK MEDIASI CUSTOMER EQUITY ATAS PENGARUH CUSTOMER RELATIONSHIP MARKETING DAN CUSTOMER SATISFACTION TERHADAP BRAND EQUITY - Tigor Sitorus; Ardy Ardy (Jurnal Manajemen, 2013)
Customer service quality in the banking industry, especially private banking is a competitive advantage to survive amid fierce competition. The type of product that is almost similar to its competitors means that a bank must have a strong point in competition. This study aims to analyze the Mediation effect of Customer Equity upon Customer Relationship Marketing and Customer Satisfaction on Brand Equity. This research was conducted in Bank Danamon Jabodetabek region, which spread in 8 (eight) districts with a total sample of 124 customers. Structural Equation Modelin (SEM) by AMOS program version 22 was used to prove the effects among variables that have high loading factors. The conclusions are as follows. First, Customer Relationship Marketing has a positive and significant effect on Customer Equity. Second, Customer Satisfaction has a positive and significant effect on Customer Equity. Third, Customer Relationship Marketing has a positive but not significant effect on Brand Equity. Fourth, Customer Satisfaction has a positive but not significant effect on Brand Equity. Fiftth, Customer Satisfaction has a positive and significant effect on brand Equity. Sixth, mediation effect of The Customer Equity upon the effect of Customer Relationship Marketing and Customer satisfaction on Brand Equtiy has more power and significant than direct effect.